INGLIS HÁM QARAQALPAQ TILLERINDEGI SANLÍ BIRLIKLERDIŃ LEKSIKA-SEMANTIKALÍQ AYÍRMAShÍLÍQLARÍ HÁM KÓRKEM TEKSTLERDEGI KOGNITIV-FUNKCIONAL ROLI - Aimuxammetova, A.M. (SCIENCE and SOCIETY, 2025)
This article presents a comparative analysis of the lexico-semantic differences and cognitive-functional roles of numeral units in English and Karakalpak literary texts. The research was conducted based on phraseological units, proverbs, and literary texts. The cultural-symbolic meanings, expressiveness, and connotative implications of numbers such as "one," "two," and "seven" were examined. Through cognitive-linguistic and linguocultural approaches, similarities and differences in language cultures were identified. The study demonstrates how numeral units reflect concepts of unity, friendship, loneliness, and scarcity. The results confirm that numeral units in both languages occupy a significant position as cultural markers within the language system.